Towards the development of a decision support tool for crop planning and irrigation scheduling in rice-based farming systems - Soriano, Jason I.
Food security may be threatened in the future due to climate change and the increasing competition for water resources. To address this, water needs to be used efficiently. A decision support tool is proposed that can estimate the potential impacts of climate change on a given cropping pattern. Scenarios were developed based on observed practices in irrigation systems and in farmers' fields, such as water-saving techniques for rice, rotational irrigation, and reduced planting area. The water balance was simulated by combining different models such as Darcy's law and a modification of the Green-Ampt method. Crop yields were estimated by using a functional equation relating evapotranspiration to yield reduction. The program was tested against field experiments on rice in Guimba, Nueva Ecija. The simulations showed an overestimation of the seasonal water use by the model, while predicted crop yields were in agreement with the actual as long as water stress did not exceed 50%. Possible upland crops after the wet season rice (onion, tomato, and maize) were then used for simulations by varying the irrigation interval and applied depths. Maize had a smaller yield reduction than onion and tomato in all scenarios. It was also observed that were almost no differences in yield reduction between 50 and 100 mm application depths, suggesting an inefficient use of water. Rice yields were tested by varying the planting dates, irrigation intervals, and irrigation amounts. Yield reductions in most scenarios exceeded 40%. Among the water-saving techniques developed, continuous saturation and alternate wetting and drying appeared to be promising alternatives.